AUTOMATIC CONTROLLER FOR STOPPING VEHICLE AT FIXED POSITION AND SYSTEM FOR ASSISTING OPERATION OF VEHICLE - KANAYAMA DOO; NAMEKI HIDEAKI; YOKOTA TOMOKO (2006)
PROBLEM TO BE SOLVED: To provide an automatic controller for stopping a vehicle at a fixed position in which a stop position error can be predicted precisely even if there are brake deceleration increase characteristics and stop precision can be secured. SOLUTION: A deceleration estimating means 12 estimates deceleration based on current speed and information about a variation in brake notch, and operates a deceleration ratio, i. e. the ratio of estimated deceleration with respect to deceleration increase characteristics of each brake notch. An average deceleration operating means 13 determines average deceleration when a vehicle is decelerated to stop by each brake notch based on brake characteristic data and the deceleration ratio. A stop position error operating means 8 operates a prediction value of a stop position error when a current brake notch is switched to the other brake notch based on state data of the vehicle and the average deceleration. A brake control command determining means 9 determines a brake control command which is then delivered from a brake control command output means 10 to a brake 11. COPYRIGHT: (C)2007,JPO&INPIT